PENGARUH PELATIHAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus pada PT R.TRI Cahya Agatha Tasikmalaya) - Miftah Mubarok; Barin Barlian; Arga Sutrisna (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
The problem of human resources is still in the spotlight for companies to survive in the era of globalization, because they have control factors that can determine the sustainability of a company. By improving the quality of human resources, it is expected that employees can work productively and professionally so that the performance they achieve will be more satisfactory according to the existing work standards in the company. The factors that influence employee performance include job training and work motivation. This study aims to determine the conditions and influence of job training and work motivation on employee performance at PT R.TRI Cahya Agatha Tasikmalaya. The type of research used is descriptive associative with a quantitative approach. The type of data used is primary data with questionnaires distributed to 32 employees of the Field Division. The data processing analysis technique is Multiple Linear Regression Analysis. Based on the results of the hypothesis, Job Training and Work Motivation both partially and simultaneously have a significant effect on employee performance.